Reconsidering stagnation in the Brezhnev era ideology and exchange - Fainberg, Dina; Kalinovsky, Artemy M. (Lexington Books, 2016)
"This collection brings together an interdisciplinary array of scholars of late socialism in the U.S.S.R. and challenges the dominant narrative of stagnation during the Brezhnev era. It demonstrates that the political and intellectual class remained ideologically committed, recognized systemic challenges, and embarked on a creative search for solutions"...Provided by publisher